Current standards and future perspectives in adjuvant treatment for biliary tract cancers. (March 2020) - Lamarca, Angela; Edeline, Julien; McNamara, Mairéad G; Hubner, Richard A; Nagino, Masato; Bridgewater, John; Primrose, John; Valle, Juan W
Graphic abstract: Three phase III trials have been recently published exploring the role of adjuvant chemotherapy in resected cholangiocarcinoma and gallbladder cancer. The trials differ in some of the baseline characteristics which may explain why only the BILCAP trial (capecitabine vs observation) was the only study showing benefit in favour of adjuvant chemotherapy in resected biliary tract cancer. Panel A shows main differences in study characteristics. Panel B provides a graphic representation of HR for Relapse-free and Overall survival, with further details summarised in Panel C . iCCA: intrahepatic cholangiocarcinoma; eCCA: extrahepatic cholangiocarcinoma; GBC: gallbladder cancer; N0: no evidence of lymph node metastases; N1: presence of lymph node metastases; R0: clear resection margins; R1: affected resection margins (including tumour within 1 mm for the BILCAP trial); Cap: capecitabine, Gem: gemcitabine; GemOc: gemcitabine and oxaliplatin; HR: Hazard Ratio; CI: confidence interval. *Hazard Ratio in the ITT (intention-to-treat) population (sensitivity analysis) is presented for the BILCAP trial (Overall Survival). Highlights: Capecitabine is the new standard of care for resected CCA and GBC. Relapse rate remains high and not all patients benefit from such adjuvant therapy. There is an urgent need for further adequately-designed and properly powered studies. Role of targeted therapies, other chemotherapy and radiotherapy requires further research in this setting. Abstract: Biliary tract cancer, including cholangiocarcinoma (CCA) and gallbladder cancer (GBC) are rare tumours with a rising incidence. Prognosis is poor, since most patients are diagnosed with advanced disease. Only 20% of patients are diagnosed with early-stage disease, suitable for curative surgery. Despite surgery performed with potentially-curative intent, relapse rates are high, with around 60–70% of patients expected to have disease recurrence. Most relapses occur in the form of distant metastases, with a predominance of liver spread. In view of high tumour recurrence, adjuvant strategies have been explored for many years, in the form of radiotherapy, chemo-radiotherapy and chemotherapy. Historically, few randomised trials were available, which included a variety of additional tumours (e.g. pancreatic and ampullary tumours); most evidence relied on phase II and retrospective studies, with no high-quality evidence available to define the real benefit derived from adjuvant strategies. Since 2017, three randomised phase III clinical trials have been reported; all recruited patients with resected biliary tract cancer (CCA and GBC) who were randomised to observation alone, or chemotherapy in the form of gemcitabine (BCAT study; included patients diagnosed with extrahepatic CCA only), gemcitabine and oxaliplatin (PRODIGE-12/ACCORD-18; included patients diagnosed with CCA and GBC) or capecitabine (BILCAP; included patients diagnosed with CCA and GBC). While gemcitabine-based chemotherapy failed to show an impact on patient outcome (relapse-free survival (RFS) or overall survival (OS)), the BILCAP study showed a benefit from adjuvant capecitabine in terms of OS (pre-planned sensitivity analysis in the intention-to-treat population and in the per-protocol analysis), with confirmed benefit in terms of RFS. Based on the BILCAP trial, international guidelines recommend adjuvant capecitabine for a period of six months following potentially curative resection of CCA as the current standard of care for resected CCA and GBC. However, BILCAP failed to show OS benefit in the intention-to-treat (non-sensitivity analysis) population (primary end-point), and this finding, as well as some inconsistencies between studies has been criticised and has led to confusion in the biliary tract cancer medical community. This review summarises the adjuvant field in biliary tract cancer, with evidence before and after 2017, and comparison between the latest randomised phase III studies. Potential explanations are presented for differential findings, and future steps are explored.